Risk Factors for Osteoporosis in Postmenopausal Women - Bijelic, Radojka (Med Arch, 2017)
INTRODUCTION: Scientific studies show that many factors related to lifestyles affect the reduction of bone mineral density and osteoporosis in postmenopausal women. GOAL: The goal of this study was to determine whether smoking, drinking coffee and alcohol in menopausal women contribute to the reduction of bone mass and osteoporosis, as well as the impact of physical activity on bone mass. MATERIAL AND METHODS: The study was carried out as case study and matched controls. The group of cases consisted of 100 females in postmenopausal age, in which by the DEXA method was newly diagnosed osteoporosis at the Clinic of Endocrinology, Diabetes and Metabolic Diseases, University Medical Center of RS during 2015-2016, while the control group consisted of 100 females in a postmenopausal age without diagnosed osteoporosis. The groups were matched by age (±2 years). In order to collect demographic data and information on risk factors for osteoporosis and lifestyle of patients was used the questionnaire Bone Mineral Density Questionnaire- Female of the Irish Association for osteoporosis. RESULTS: Testing the significance of differences in terms of smoking showed that the studied groups are statistically significantly different in terms of smoking (χ(2)=24.025, p=0.000). In terms of consumption of coffee, a statistically significant difference was found between the group of cases and control group (χ(2)=0.615, p=0.735). When observing the obtained information about the consumption of alcohol, we find that this preventable risk factor in the present study did not show as significant for osteoporosis in postmenopausal women (χ(2)=4.35, p=0.114). Statistical analysis shows that there are significant differences between the group of cases and control group in terms of physical activity (χ(2)=7.30, p=0.026). Analysis of the data of our study by univariate logistic regressions showed that smoking (p=0.000) was statistically significantly associated with osteoporosis, while physical activity is a protective factor for bone mass (p=0.036). Results of multivariate logistic regression showed that the independent risk factors for osteoporosis in postmenopausal women is smoking (OR=1.665; p=0.006). CONCLUSION: The results of our study show that smoking is an independent risk factor for osteoporosis in postmenopausal women, and physical activity is a protective factor for bone mass retention. Through education and certain preventive measures should be stressed the importance of these factors on bone health from the earliest period.